Evaluasi Daya Gabung dan Heterosis Lima Galur Jagung Manis (Zea mays var. saccharata) Hasil Persilangan Dialel - Iriany, R. Neni (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
The objective of this research was to estimate general combining ability (GCA), specifi c combining ability (SCA), and heterosis of fi ve sweet corn inbreds in order to be selected to develop hybrid varieties. Five inbred lines as parent were Mr12/SC/BC4-6-1B-1, Mr14/SC/BC4-6-1B-1, Mr4/SC/BC4-2-1B-1, Mr11/SC/BC4-2-1B-1, and Mr12/SC/BC3-3-1B-1. The experiment was conducted from April to June 2010 using a Randomized Complete Block Design with two replications at Indonesian Cereal Research Institute (ICERI) experimental station, Maros, South Sulawesi. Analyses of GCA and SCA were based on the Griffi ng’s fixed model of Diallel Design Method I. Heterosis values were predicted based on the average values of their parents whereas heterobeltiosis were predicted based on the average values of the highest parents. Cross B x D (Mr14/SC/BC4-6-1B-1 x Mr11/SC/BC4-2-1B-1) had the highest SCA for yield 990.67. Cross A x B (Mr12/SC/BC4-6-1B-1 x Mr14/SC/BC4-6-1B-1) had the highest SCA for ear diameter 0.36. Cross A x D (Mr12/SC/BC4-6-1B-1 x Mr11/SC/BC4-2-1B- 1) had the highest heterosis and heterobeltiosis for yield, while Cross A x D (Mr12/SC/BC4-6-1B-1 x Mr11/SC/BC4-2-1B-1) had the highest heterosis and heterobeltiosis for ear length. Cross A x B (Mr12/SC/BC4-6-1B-1 x Mr14/SC/BC4-6-1B-1) and E x A (Mr12/SC/BC3-3-1B-1 xMr12/SC/BC4-6-1B-1) had the highest heterosis and heterobeltiosis for ear diameter. Keywords: combining ability, diallel crossing, heterosis, sweet corn